(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
This essay aims to investigate the connection between a local archive and global history, with a glocal perspective in a school environment. The work will deal with the archive of a high school in Milan, Italy, and examine how this community, with its principal, teachers and students, looked at (and was involved with) international events between 1935 and 1945. This was the period when fascist Italy declared war on Ethiopia and took part in the Second World War in its quest for an Empire and, later, for a new role in a Nazi-ruled Europe. Fascist foreign policy, which meant “war policy” in that period, and the way the Italian schools dealt with it became part of the totalitarian design of the regime. Changes in the local perspective regarding international events reflect changes in the regime’s political agenda.